Early Risk Detection of Burnout: Development of the Burnout Prevention Questionnaire for Coaches - Schaffran, Paul; Kleinert, Jens; Altfeld, Sebastian; Zepp, Christian; Kallus, Konrad Wolfgang; Kellmann, Michael (Frontiers in Psychology, 2019)
Introduction: Previous research has shown that burnout develops as the result of a continuous imbalance between chronic stress and appropriate coping resources. Hence, the essential factors to measure burnout encompassed the factors stress and recovery within our studies. However, the Burnout Prevention Questionnaire for Coaches (BPQ-C) does not represent a new questionnaire from scratch, but rather a re-evaluated, condensed, and subsequently combined instrument with scales derived from validated psychometric instruments. Methods: The objective of study 1 (N = 233) was to create and evaluate the psychometric structure of the BPQ-C. The aim of study 2 (N = 473) consisted in the validation of the BPQ-C via a Confirmatory Factor Analysis. Results: The Exploratory Factor Analysis resulted in a model with three dimensions (Pre-Burnout, Resources, and Burnout). Via the subsequent Confirmatory Factor Analysis, the model could be confirmed with good fit indices (χ2 = 96.898, df = 19, p < 0.001, CFI = 0.973, SRMR = 0.044, RMSEA = 0.093, LO90 = 0.075, HI90 = 0.112). Conclusion: The BPQ-C includes a number of previously established risk and protective factors within a single psychometric instrument. The systematic application of the BPQ-C can help to detect critical conditions at an early stage in order to derive individualized and beneficial interventions for the respective coaches.